Varetægtsfængsling og virkelighed - Nielsen, Henrik Karl Nielsen (Nordisk Tidsskrift for Kriminalvidenskab, 2024)
Abstract According to a study published by Emelí Lönnqvist in 2023, the percentage of inmates in pre-trial detention (imprisonment on remand) in Denmark differs significantly from the other Nordic countries. This is an issue of ongoing debate among Danish defence lawyers. The present study analyses 46 cases before the City Court of Copenhagen in 2023-2024, in which the public prosecutor has requested a pre-trial detention of the person charged with an offence. It is apparent that the relevant provisions on pre-trial detention are not applied restrictively despite the fact that a pre-trial detention is a deviation from the right of personal freedom. It is also apparent that the alternatives to pre-trial detention listed in section 765(2) of the Administration of Justice Act are not applied. Furthermore, it is apparent that decisions on pre-trial detention only rarely indicate the reasons that have justified a pre-trial detention.